2013
DOI: 10.11648/j.ajbls.20130101.12
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Apparent Digestibility Coefficient of Plant Feed Ingredients (Soybean and Sunflower Meal) for Labeo Rohita

Abstract: Abstract:The present study was carried out to estimate the apparent nutrient digestibility of soybean meal and sunflower meal for Labeo rohita. Prior to being fed with test diets, the fish were acclimatized on reference diet for about one week. Test diet-1 (soybean meal) and test diet-2 (sunflower meal) was prepared by mixing reference diet and test feed ingredients (soybean meal and sunflower meal) in a 70:30 ratio. Representative samples of feed and feces of fish were analyzed for the dry matter, crude prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…For example, the lower dry matter ADC of soybean in the present study could be explained by the higher crude fibre content of the product evaluated in this study of 69 g/kg, compared with 39 g/kg in the study by Köprücü and Őzdemir [13]. Other studies on fish have also indicated the negative correlation between crude fibre content and dry matter ADC [31][32][33]. In general, results of dry matter ADC can be used to estimate the amount of solid waste released to the environment and to help determine the environmental impacts of aquaculture production [7,32].…”
Section: Discussioncontrasting
confidence: 43%
“…For example, the lower dry matter ADC of soybean in the present study could be explained by the higher crude fibre content of the product evaluated in this study of 69 g/kg, compared with 39 g/kg in the study by Köprücü and Őzdemir [13]. Other studies on fish have also indicated the negative correlation between crude fibre content and dry matter ADC [31][32][33]. In general, results of dry matter ADC can be used to estimate the amount of solid waste released to the environment and to help determine the environmental impacts of aquaculture production [7,32].…”
Section: Discussioncontrasting
confidence: 43%
“…Information about the incorporation of guar meal in fish feed is limited. Except for a few studies on substitution of fish meal and soybean meal with gaur meal in the diets of common carp and Nile tilapia (Al-Hafedh & Siddiqui, 1998;El-Saidy et al, 2005;El-Sayed et al, 2016), on performance of mrigal fed raw and hydrothermally processed guar seeds (Garg et al, 2002), on comparison of digestibility of nutrients in rohu fed meat meal and guar meal (Asad et al, 2005) and on growth of rohu fed on unprocessed guar meal and commercial feed enzyme-treated guar meal incorporated in diets replacing fishmeal (Chovatiya, 2011), no other information is available on incorporation of gaur meal in aquaculture feed.…”
Section: Introductionmentioning
confidence: 99%
“…Global production of guar was about 2.34 million t in 2014 of which >80% was produced by India followed by Pakistan (15%) (Guar Outlook, 2015). GRM was used to certain extent in livestock feed (Lee et al, 2005) as well as in fish feed (Asad et al, 2005;El-Saidy et al, 2005;Kalanjium et al, 2014) but its usage is very rare as an ingredient in shrimp feed. In our previous study, nutrient utilisation of GRM in the diet of Penaeus vannamei was evaluated and the results clearly indicated deleterious effects on the measures of growth, nutrient utilisation and feed efficiency due to the inclusion of GRM (Jannathulla et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, nutrient utilisation of GRM in the diet of Penaeus vannamei was evaluated and the results clearly indicated deleterious effects on the measures of growth, nutrient utilisation and feed efficiency due to the inclusion of GRM (Jannathulla et al, 2016). Poor performance with GRM was attributed to undesirable chemical constituents especially, anti-nutritional factors (Asad et al, 2005;Jannathulla et al, 2016). The deleterious effects of anti-nutritional factors have been reported earlier in shrimp (Lim and Dominy, 1990;Chen et al, 1996).…”
Section: Introductionmentioning
confidence: 99%